Building stone used in architectural objects in the town of Wieluń - Śpiewak, Adam (Wydawnictwa AGH, 2014)
The architectural space of the center of Wieluń and chosen objects located in the town were analyzed. Research was carried out on the identification of building stones in this particular area. On the basis of the research, it is possible to find over fifty kinds of various stone materials, including sedimentary, igneous and metamorphic rocks. These were classified and counted. For the first time, a coefficient of Used Kinds of Stone in architectural Objects (UKSO) was suggested. Its purpose was to show, from the engineering point of view, the amount of the stone in urban architecture. The most interesting stone pictures display their variations in color, structure and texture. The gathered results confirm their geological inheritance and increase the tourist attractiveness of the town.
Geotourism / Geoturystyka
Keywords: building stone; geotourism; geology; architecture; Wieluń